CEO School Insights from 20 Global Business Leaders - Shekshnia, Stanislav (Springer Singapore, 2018)
"CEO School is the kind of concise, focused look at what works, and what doesn't, that busy leaders will appreciate. Invaluable lessons from those who've lived it." - General Stanley McCrystal, former Commander, US Joint Special Operations Command (JSOC), author of the New York Times bestseller Team of Teams "Reading through the book made me feel: I've been there, I have done that, but I wish I had read this book before." -Arzu Aslan, CEO of Tat Food, Turkey "This thought-provoking book challenges some fundamental assumptions about what makes business leaders effective. Fascinating read!" -Marshall Goldsmith, Thinkers 50 #1 Leadership Thinker in the World and author of the #1 New York Times bestseller Triggers "The authors have provided us with new and interesting angles on how to reach the top and then stay there, carefully crafted in the style of an easy conversation with a wise mentor." -Kevin Murray, ex-CEO, executive coach and bestselling author of The Language of Leaders and Communicate to Inspire What makes a successful CEO and how do you become one in today's global economy? This book gathers answers from an extensive global project involving 20 top CEOs - one from each G20 country - into seven easy-to-read "leadership masterclasses". The authors present their surprising findings about the essential character traits, experience and skills required in a simple, entertaining, step-by-step guide for aspiring business leaders, educators and recruiters. Stanislav Shekshnia is a professor at INSEAD, senior partner at Ward Howell International and former CEO of two telcoms companies. Kirill Kravchenko is Deputy CEO for Organizational Affairs of Gazprom Neft and former CEO of Serbian multinational oil company, NIS, where he remains on the board of directors. Elin Williams is a freelance writer specialising in business, and careers. .